Face masks in the general healthy population. Scientific and ethical issues - Miguel Angel Royo-Bordonada; Fernando José García-López; Fátima Cortés; Gustavo Andrés Zaragoza (Elsevier, 2021)
In most European countries, facemasks use is recommended or mandatory in enclosed spaces where physical distancing is not possible. In Spain, this measure was first extended to open public spaces and later made mandatory regardless of whether or not the interpersonal safety distance can be kept. At present, there is no evidence on the effectiveness of universal masking of healthy people in the community to prevent infection with respiratory viruses, including SARS-CoV-2. The mandatory use of masks poses some ethical questions. Firstly, it entails a paternalistic action. Secondly, application of the principle of precaution becomes questionable when there is no clear benefit-risk relationship. Thirdly, compulsoriness can interfere with equity of public health actions. Fourthly, it can result in social stigma and discrimination against those who do not wear one, even though they well may have good reasons for doing so. Lastly, this measure may generate confusion in the population, along with an altered perception of the risk. The World Health Organization recommends its use in public places with a high potential risk of transmission and where other prevention measures, such as physical distancing, are not possible. Mandatory use of masks in public open spaces, regardless of the risk of transmission or of whether or not the interpersonal safety distance can be kept, is an intrusive measure that restricts individual freedoms, and would not appear to be justified on the basis of available scientific evidence. What we need are recommendations explaining where, when, how and what type of mask to wear. Resumen: En la mayoría de los países europeos, el uso de mascarillas es recomendado u obligatorio en espacios cerrados donde no es posible mantener la distancia física de seguridad. En España, la obligatoriedad se amplió primero a los espacios públicos abiertos y más tarde independientemente de la distancia de seguridad. En la actualidad no hay pruebas de la efectividad del uso universal de mascarilla para prevenir el contagio de virus respiratorios, incluido el SARS-CoV-2. El uso obligatorio de mascarilla plantea cuestiones éticas. Primero, implica una acción paternalista. Segundo, la aplicación del principio de precaución es cuestionable cuando no existe una relación clara beneficio-riesgo. Tercero, puede interferir en la equidad de las acciones de salud pública. Cuarto, puede dar lugar a un estigma social y a la discriminación de quienes no hacen uso de ella, aunque tengan buenas razones para ello. Por último, esta medida puede generar confusión en la población, junto con una percepción alterada del riesgo. La Organización Mundial de la Salud recomienda su uso en lugares públicos con un alto riesgo de transmisión y donde no sea posible aplicar otras medidas de prevención, como la distancia física. El uso obligatorio de mascarilla en espacios públicos abiertos, independientemente del riesgo de transmisión o de que se pueda o no mantener la distancia de seguridad, es una medida intrusiva que restringe las libertades individuales y no parece justificarse sobre la base de las pruebas científicas disponibles. Lo que necesitamos son recomendaciones explicando dónde, cuándo, cómo y qué tipo de mascarilla usar.